Pengaruh e-service quality dan e-trust terhadap e-loyalty dengan e-satisfaction sebagai variabel intervening pada pengguna e-commerce shopee di Surakarta - Rizkiawan, Ilham Karin; Putranti, Latifah; Puspita, Dela (Journal of Management and Digital Business, 2022)
This study is entitled The Effect of E-Service Quality and E-Trust on E-Loyalty with E-Satisfaction as an Intervening Variable for Shopee E-Commerce Users in Surakarta. This study aims to determine electronic service quality and trust's effect on electronic loyalty, with electronic satisfaction as an intervening variable. This research is quantitative research with a survey method. The population of this study is consumers who have made purchases on the Shopee website more than once. The sampling technique used purposeful sampling with a total sample of 205 people. The data collection technique uses an online questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is path analysis. The results of the study show that there is a positive effect of e-service quality and e-trust on e-satisfaction. There is a positive effect of e-service quality and E-Satisfaction on E-Loyalty. There is a positive and significant effect of e-service quality and e-trust on e-loyalty, which is mediated by the e-satisfaction of Shopee E-Commerce users in Surakarta.